Critical Review: Factors Affecting Online Purchase Intention Generation Z - Yolanda Veybitha; Lizar Alfansi; Muhartini Salim; Effed Darta (Journal of International Conference Proceedings (JICP), 2021)
This review aims to examine in depth what factors influence Generation Z's online purchase intention. In addition, the author also examines the online shopping research framework model as a reference to be developed in further research. The author collects the results of previous studies regarding online purchase intentions for 10 years (2011 – 2021) from various international journal sources. Based on the results of previous studies, the research model framework uses TAM (Technology Acceptence Model) variables, trust, social factors, security, and website quality. The main finding in previous research shows that the security factor greatly determines a person's online purchase intention. The security factor here is not just a product guarantee to consumers, but also about consumer data that is not easily hacked by irresponsible parties. The convenience of the payment system also influences online purchase intentions. In addition, utilitarian and hedonic motives encourage individuals to make online purchases. The utilitarian motive is concerned with consumer needs, while the hedonic motive emphasizes pleasure.